2006
DOI: 10.4028/www.scientific.net/msf.519-521.1083
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Fatigue Initiation in Al-Si Casting Alloys

Abstract: Fatigue initiation behaviour in three multi-component Al-Si casting alloys with varying Si content is compared using a range of microscopy and analytical techniques. A higher proportion of stiffer secondary phases leads to load transfer effects reducing particle cracking and particle/matrix debonding. Si appears stronger than the Al9FeNi phase, which cracks and debonds to form initiation sites preferentially over Si. Reducing Si content results in clusters of intermetallics forming, and increased porosity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
55
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 9 publications
(10 reference statements)
5
55
1
Order By: Relevance
“…Previous studies [1,3,7,8] on model piston alloys with high Cu and Ni levels (3.9 wt.% Cu and 2.8 wt.%Ni) confirmed that fatigue crack initiation occurs at Si particles and intermetallic particles such as Al 9 FeNi and Al 3 (CuNi) 2 . Some of the model alloys investigated contained reduced Si levels of 6.9 wt.% and 0.67 wt.% as shown in Table 1.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Previous studies [1,3,7,8] on model piston alloys with high Cu and Ni levels (3.9 wt.% Cu and 2.8 wt.%Ni) confirmed that fatigue crack initiation occurs at Si particles and intermetallic particles such as Al 9 FeNi and Al 3 (CuNi) 2 . Some of the model alloys investigated contained reduced Si levels of 6.9 wt.% and 0.67 wt.% as shown in Table 1.…”
Section: Introductionmentioning
confidence: 69%
“…Light vehicle engine pistons are commonly cast from near-eutectic multicomponent Al-Si alloys typically containing high levels of Cu and Ni [1]. The rapid increase in performance requirements in diesel engines together with light-weighting and strict emission regulations has necessitated development of new piston designs and materials that can withstand the increasingly harsh combination of fluctuating thermal stresses and cylinder pressure [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations